Bakhtin and his Others (inter)subjectivity, chronotope, dialogism - Steinby, Liisa; Klapuri, Tintti (Anthem Press, 2013)
Bakhtin and his Others offers fresh theoretical insights into Bakhtins ideas on (inter)subjectivity and temporality, research into his theoretical backgrounds, and case studies where these insights are employed in literary analysis
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Bakhtin, M. M. / (Mikhail Mikhaĭlovich) / 1895-1975 / Criticism and interpretation; Bachtin, Michail Michajlovič -- 1895-1975; Literatur; Ästhetik; Literature / History and criticism / Theory, etc; Literature / Aesthetics; Subject (Philosophy) in literature; Intersubjectivity in literature; Dialogism (Literary analysis); Intersubjektivität; Zeit -- Motiv; Dialogisches Prinzip; Aufsatzsammlung